Martínez Usurralde, M. J., Viana Orta, M. I. y Villarroel, C. B. (2015). La UNESCO. Educación en todos los sentidos. Valencia: Tirant Humanidades. 180 pp. ISBN: 978-84-16349-49-4 - González Pérez, María Inmaculada (Pedagogia Social Revista Interuniversitaria, 2017)
Reseña